2021
DOI: 10.1007/s11739-021-02733-9
|View full text |Cite
|
Sign up to set email alerts
|

Early echocardiographic findings in patients hospitalized for COVID-19 pneumonia: a prospective, single center study

Abstract: Background Cardiac dysfunction, mainly assessed by biomarker alterations, has been described in COVID-19 infection. However, there are still areas of uncertainty regarding its effective role in disease evolution. Aim of this study was to evaluate early echocardiographic parameters in COVID pneumonia and their association with severity disease and prognosis. Methods An echocardiographic examination was performed within 72 h from admission in 64 consecutive patients hospitalized for COVID-19 pneumonia in our med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 studies reported data about the prevalence of RVD 14 42 , while 7 reported about all-cause mortality according to RVD status 17 , 19 , 20 , 30 , 33 , 35 , 36 . 11 studies were held in Europe 16 , 18 21 , 33 36 , 38 , 40 , 8 in North America 23 , 25 , 26 , 28 , 29 , 37 , 41 , 42 , 3 in Asia 30 32 , and 7 in other geographical locations 14 , 15 , 17 , 22 , 24 , 27 , 39 , including 2 multinational studies 24 , 27 . Cohorts included were quite homogeneous in terms of mean age of the included patients (ranging from 52 years old to 68 years old); among sex, males were generally more represented than females (up to 84%).…”
Section: Resultsmentioning
confidence: 99%
“…The definition of RVD was heterogeneous across studies, both in terms of parameters and cut-offs used to defined RVD. 13 studies used a combination of several parameters 15 , 18 , 19 , 21 , 24 , 28 , 30 , 33 35 , 38 , 40 , 42 , 8 studies defined RVD according to TAPSE cut-off 14 , 16 , 22 , 23 , 31 , 32 , 36 , 39 , while other or unclear definitions of RVD was used in 8 studies 17 , 20 , 25 27 , 29 , 37 , 41 . In one study, a surrogate of Right Ventricular-Arterial uncoupling, which in turn relates the degree of RVD to the increase of pulmonary pressure, was addressed 20 .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of hypoxia on pulmonary artery pressure in pneumonia patients increases ventricular wall tension, and this may explain the elevation of BNP in pneumonia patients independent of heart failure 16,40 . High pulmonary artery pressure is also seen in COVID-patients, which is an indicator of poor prognosis and mortality 41,42 . This mechanism may explain the elevation of BNP levels in critically ill patients that resulted in mortality in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In both critical and non-critical care settings, transthoracic echocardiography (TTE) is considered a frontline cardiovascular imaging tool in COVID-19 [333][334][335][336][337][338][339]. Abnormal TTE findings are common and alter clinical management in up to one third of cases [333,334].…”
Section: Transthoracic Echocardiography (Tte)mentioning
confidence: 99%